Analisis Literasi Lingkungan pada Siswa Kelas V SDN 19 Cakranegara - Azuzilawati Bti Rashid; Siti Rohana Hariana Intiana; Khairun Nisa (Mataram University, 2026)
This study aims to describe the level of environmental literacy understanding among fifth-grade students at SDN 19 Cakranegara, the factors influencing it, and the role of teachers in improving students’ environmental literacy. This study employed a descriptive qualitative approach. The research subjects consisted of fifth-grade teachers and fifth-grade students at SDN 19 Cakranegara. Data were collected through observation, interviews, questionnaires, and documentation. Data analysis used the Miles and Huberman model, which includes data collection, data condensation, data display, and conclusion drawing, while the validity of the data was tested through source triangulation and technique triangulation. The results of the study indicate that the level of environmental literacy understanding among fifth-grade students at SDN 19 Cakranegara is categorized as very good, as reflected in the achievement of the following aspects: knowledge (100%), skills (98.7%), character (94.7%), and behavior (98.7%). In the knowledge aspect, students were able to understand the causes of environmental damage and ways to preserve the environment; in the skills aspect, students were able to carry out cleanliness activities independently and in an organized manner; in the character aspect, students demonstrated caring attitudes, discipline, and responsibility toward the school environment; while in the behavioral aspect, students had developed positive habits such as disposing of waste properly, conserving energy, and actively participating in school environmental activities. The factors influencing students’ environmental literacy understanding include the role of teachers, parental support, and the school environment. Teachers act as facilitators, mentors, role models, and supervisors in shaping students’ environmental awareness through learning activities, habituation, and direct involvement in school programs. Parental support is reflected in the provision of cleanliness facilities and the encouragement of environmentally friendly behavior at home. In addition, a clean and well-organized school environment, supported by the involvement of all members of the school community, further strengthens the development of students’ environmental literacy. Based on the findings, it can be concluded that the environmental literacy of fifth-grade students at SDN 19 Cakranegara has developed very well through processes of habituation, role modeling, supervision, and support from various parties within both the school and family environments.